The proposed standing multilateral mechanism and its potential relationship with the existing universe of investor: State dispute settlement - Danish; Daniel Uribe Terán (South Centre, 2022)
The reform option on the Standing Multilateral Mechanism (SMM) currently under discussion at UNCITRAL's Working Group III (WGIII) has raised a number of important, systemic concerns for the procedural reforms of investor-State dispute settlement. This paper first seeks to situate the discussions on the SMM within its historical and contemporary contexts. Then it considers UNCITRAL Working Paper 213 and the legal provisions it contains, which form the basis of ongoing discussions of this reform option at WGIII. Further, it explores the potential relationship of this proposed SMM with different facets of the existing international investment law regime. The paper concludes by providing some elements which require further consideration in this process, particularly for safeguarding the interests of developing countries.
Keywords: 300; Appellate Mechanism; Bilateral Investment Treaties (BITs); International Investment Agreements (IIAs); Investment; Investment Agreement; Investment Arbitration; Investment Chapters; Investment Law and Policy; Investment Policy and Protection; Investment Treaties; Investments; Investor-State Dispute Settlement (ISDS) System; ISDS Reform; Multilateral Investment Court (MIC); Standing Multilateral Mechanism (SMM); UNCITRAL WGIII; United Nations Commission on International Trade Law (UNCITRAL); Working Group III (WGIII)